The Effect of a Foot Bath on Sleep Quality in the Elderly: A Single-Blind Randomized Controlled Trial - Sevilay Hintistan; Aynur Cin; Hatice Demirağ (Journal of Nursology)
Objective: This study was conducted as a single-blind, randomized controlled parallel-group study with 50 elderly individuals to investigate the effect of foot bath on sleep quality.Methods: The data were collected using the “Elderly Information Form” and the “Pittsburgh Sleep Quality Index (PSQI)” between 1 May 2022-1 July 2022 at a State Hospital in Gümüşhane province. The elderly in the foot bath group were given a foot bath with 41-42°C water for 20 minutes 50 minutes before normal sleep hours. No application was made to the control group except for the administration of data collection tools. The data were analyzed with Chi-square, Friedman, Wilcoxon Sign, and Mann-Whitney U tests.Results: It was determined that at least one of the total PSQI measurements and median scores of all subcomponents obtained from the elderly in the foot bath group differed depending on time (P.05). Again, All PSQI subcomponents and total PSQI scores, except for the subcomponent “Habitual Sleep Efficiency (C4)”, decreased throughout the application in the elderly in the foot bath group.Conclusion: As a result, a foot bath improved sleep quality in the elderly. In line with the findings from this study, it is recommended to compare the foot bath with multiple experimental groups for a longer period of time.